2022
DOI: 10.1128/mbio.01121-22
|View full text |Cite
|
Sign up to set email alerts
|

Cobalamin Riboswitches Are Broadly Sensitive to Corrinoid Cofactors to Enable an Efficient Gene Regulatory Strategy

Abstract: Some bacterial mRNAs contain a region called a riboswitch which controls gene expression by binding to a metabolite in the cell. Typically, riboswitches sense and respond to a limited range of cellular metabolites, often just one type.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 129 publications
0
9
0
Order By: Relevance
“…Complementary to the class-II Cbl riboswitch findings is the observation that an increase in AdoCbl selectivity, integral to class-I Cbl riboswitches, appears to be deleterious to plasticity. It has been hypothesized that class-I Cbl riboswitches are incapable of discriminating between AdoCbl and similar antivitamin B 12 forms, and some evidence supports this. ,, However, we show that the E. coli btuB Cbl riboswitch did not bind any of the Cbl derivatives tested through SHAPE and fluorescent methods.…”
Section: Discussionmentioning
confidence: 41%
See 1 more Smart Citation
“…Complementary to the class-II Cbl riboswitch findings is the observation that an increase in AdoCbl selectivity, integral to class-I Cbl riboswitches, appears to be deleterious to plasticity. It has been hypothesized that class-I Cbl riboswitches are incapable of discriminating between AdoCbl and similar antivitamin B 12 forms, and some evidence supports this. ,, However, we show that the E. coli btuB Cbl riboswitch did not bind any of the Cbl derivatives tested through SHAPE and fluorescent methods.…”
Section: Discussionmentioning
confidence: 41%
“…It has been hypothesized that class-I Cbl riboswitches are incapable of discriminating between AdoCbl and similar antivitamin B 12 forms, and some evidence supports this. 24,26,53 However, we show that the E. coli btuB Cbl riboswitch did not bind any of the Cbl derivatives tested through SHAPE and fluorescent methods. This suggests that displacement of the equivalent A20 position in this riboswitch is disallowed.…”
Section: ■ Summary and Outlookmentioning
confidence: 99%
“…As observed with AdoRhbl , [9] the bioassay indicated that AcRhbl was actively imported by the bacteria and produced inhibitory growth effects. These observations indicate that AcRhbl interferes with bacterial metabolism, most likely by impairing the B 12 ‐riboswitch regulated import of CNCbl [55,56] . In this scenario AcRhbl may regulate the riboswitch either directly, or indirectly as a possible metabolic precursor [57] to AdoRhbl , the structural AdoCbl ‐mimic.…”
Section: Discussionmentioning
confidence: 94%
“…These observations indicate that AcRhbl interferes with bacterial metabolism, most likely by impairing the B 12 -riboswitch regulated import of CNCbl. [55,56] In this scenario AcRhbl may regulate the riboswitch either directly, or indirectly as a possible metabolic precursor [57] to AdoRhbl, the structural AdoCbl-mimic. Further studies are planned to elucidate more precisely the inhibitory mechanism considered here.…”
Section: Discussionmentioning
confidence: 99%
“…It has been hypothesized that class-I Cbl riboswitches are incapable of discriminating between AdoCbl and similar antivitamin B12 forms and some evidence supports this. 25,27,52 However, we show that the E. coli btuB Cbl riboswitch did not bind any of the Cbl derivatives tested through either SHAPE or fluorescent methods. This suggests that displacement of the equivalent A20 position in this riboswitch is disallowed, which may be a result of the plasticity of the nucleotide on the opposite strand in J6/3 that is required to accommodate the Ado.…”
Section: Discussionmentioning
confidence: 99%